(untitled) - McKinty, Adrian (New York, 2008)
After teenage friends Jamie and Ramsay travel back to Altair to save the last citizens of that dying planet, the ancient race who built the mysterious, wormhole-seeking Salmon returns with a terrible proposition for Jamie.
Keywords: Space and time,Science fiction,Không gian và thời gian,Khoa học viễn tưởng; Fiction,Viễn tưởng